2019
DOI: 10.4183/aeb.2019.145
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Bioelectric Impedance for Follow-Up of Dieters: a Prospective Study

Abstract: Context. Visceral adipose tissue (VAT) is a strong predictor of carbohydrate metabolism disorders. Abdominal bioelectrical impedance analysis (A-BIA) is a simple method for the measurement of VAT and is a promising tool in screening and follow-up of abdominal obesity. However the role of A-BIA in dieting individuals has not been evaluated adequately in longitudinal followup studies.Objective. The aim of this study is to determine the role of A-BIA in identifying the changes in metabolic predictors after diet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(27 reference statements)
2
0
0
1
Order By: Relevance
“…In addition, we reported that the change in the final HOMA-IR score appears to be a better marker of metabolic improvement than other variables studied, such as triglycerides, total cholesterol, HDL cholesterol, LDL cholesterol, CRP, adiponectin, and leptin. Similar to our results, Bozkuş et al found that a change in the HOMA-IR correlated with change in body weight and BMI at the end of a short-term intervention (12 weeks) [67], while the reduction in LDL cholesterol and the elevation in HDL cholesterol levels were not statistically significant. As shown elsewhere, the HOMA-IR score changes after short-term interventions were predictive of weight changes 6 months after the end of the intensive weight loss phase [10].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, we reported that the change in the final HOMA-IR score appears to be a better marker of metabolic improvement than other variables studied, such as triglycerides, total cholesterol, HDL cholesterol, LDL cholesterol, CRP, adiponectin, and leptin. Similar to our results, Bozkuş et al found that a change in the HOMA-IR correlated with change in body weight and BMI at the end of a short-term intervention (12 weeks) [67], while the reduction in LDL cholesterol and the elevation in HDL cholesterol levels were not statistically significant. As shown elsewhere, the HOMA-IR score changes after short-term interventions were predictive of weight changes 6 months after the end of the intensive weight loss phase [10].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the predictors of effective body weight loss or body weight regain assessed previously are often not sufficiently substantiated or have a low prediction power [ 66 ]. In the present study, changes in BW and fat mass (body fat mass, fat percentage, and visceral fat level) at the end of the WLP were associated with change in the HOMA-IR (homeostatic model assessment for insulin resistance) score, which in the case of BW but not body fat mass was similar to the results in other studies [ 67 ]. In addition, we reported that the change in the final HOMA-IR score appears to be a better marker of metabolic improvement than other variables studied, such as triglycerides, total cholesterol, HDL cholesterol, LDL cholesterol, CRP, adiponectin, and leptin.…”
Section: Discussionsupporting
confidence: 89%
“…Cihazın, ölçümler arası değişkenliği çok düşük olup, ölçen kişiden etkilenmiyor olması da önemli bir avantajıdır. Kliniğimizde yaptığımız, diyet sonrası antropometrik ölçümlerdeki değişim ile HOMA skorundaki değişim arasındaki ilişkiyi incelediğimiz çalışmada, HOMA skorundaki değişim ile en iyi bağımsız ilişki, abdominal BİA cihazı ile ölçülen visseral yağ arasındaki saptanmıştır [28]. Bu nedenle tedavi sonrası değişiklikleri göstermesi açısından faydalı olabileceğini düşünüyoruz.…”
Section: Bu çAlışma Başkent üNiversitesiunclassified